One NF1 Mutation may Conceal Another - Pacot, Laurence (Genes (Basel), 2019)
Neurofibromatosis type 1 (NF1) is an autosomal dominant disease with complete penetrance but high variable expressivity. NF1 is caused by loss-of-function mutations in the NF1 gene, a negative regulator of the RAS-MAPK pathway. The NF1 gene has one of the highest mutation rates in human disorders, which may explain the outbreak of independent de novo variants in the same family. Here, we report the co-occurrence of pathogenic variants in the NF1 and SPRED1 genes in six families with NF1 and Legius syndrome, using next-generation sequencing. In five of these families, we observed the co-occurrence of two independent NF1 variants. All NF1 variants were classified as pathogenic, according to the American College of Medical Genetics and Genomics and the Association for Molecular Pathology (ACMG-AMP) guidelines. In the sixth family, one sibling inherited a complete deletion of the NF1 gene from her mother and carried a variant of unknown significance in the SPRED1 gene. This variant was also present in her brother, who was diagnosed with Legius syndrome, a differential diagnosis of NF1. This work illustrates the complexity of molecular diagnosis in a not-so-rare genetic disease.